Text-fig. 12. a, b: Salix aff. caprea. a: Oriolo MSF 857. b: Oriolo MSF 860. c, d: Salix aff. alba. c: Oriolo MSF 854. d: Oriolo MSF 854. e, f: Salix aff. viminalis vel eleagnos. e: Oriolo MSF 803. f: Oriolo MSF 801. g: Salix aff. triandra Oriolo MSF 626. h–k: Salix spp. div. indet. h: Oriolo MSF 865. i: Oriolo MSF 807. j: Oriolo MSF 804. k: Oriolo MSF 802. Scale bars 10 mm (a–e, h, i–k), 50 mm (f, g). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 12. a, b: Salix aff. caprea. a: Oriolo MSF 857. b: Oriolo MSF 860. c, d: Salix aff. alba. c: Oriolo MSF 854. d: Oriolo MSF 854. e, f: Salix aff. viminalis vel eleagnos. e: Oriolo MSF 803. f: Oriolo MSF 801. g: Salix aff. triandra Oriolo MSF 626. h–k: Salix spp. div. indet. h: Oriolo MSF 865. i: Oriolo MSF 807. j: Oriolo MSF 804. k: Oriolo MSF 802. Scale bars 10 mm (a–e, h, i–k), 50 mm (f, g). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 239, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867